Festival Eksperimen Fisika di SMPN 6 Kupang Tengah - Pasaribu, Rosenti; Dewa, Egidius; Mukin, Maria Ursula Jawa (Universitas Nusantara PGRI Kediri, 2023)
Physics experiment festival activities have been carried out at SMPN 6 Kupang Tengah. This activity is in the form of community service activities. Festival activities consist of physics demonstrations, media and physics learning products exhibitions, and simple physics experiments. The selection of festival activities was determined based on the observation results. The results of the observations were the unavailability of Physics practicum tools and the absence of Integrated Science teachers with a Physics education background at the school. This condition causes Integrated Science learning to be minimal with physics practicum activities. The variable that is measured in this activity is student interest. The results of the analysis of students' interest in the Physics Experiment Festival activities were 85% of students very interested and 15% of students interested. The results also show that interesting physics learning, which is complemented by demonstrations and experiments, will increase students' interest in learning. Therefore, it is necessary for teachers to complement science learning with demonstrations or experiments involving students.